Poznoantična utrjena naselbina Tonovcov grad pri Kobaridu = Late Antique fortified settlement Tonovcov grad near Kobarid Najdbe = Finds - Milavec, Tina (Opera Instituti Archaeologici Sloveniae, 2011)
All finds from the field investigations at Tonovcov grad near Kobarid are published in the second volume. An exceptional number of finds represents the base for studies of the material culture in Late Antiquity (metallic finds, glass finds, pottery finds), as well as for the others archaeological (anthropological and zoological) remains.